2021
DOI: 10.3390/ma14164589
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Surface Modification of Polyetheretherketone (PEEK) Implants by Hydroxyapatite/Silica Coating—An In Vivo Animal Study

Abstract: Polyetheretherketone (PEEK) has the potential to overcome some of the disadvantages of titanium interbody implants in anterior cervical and discectomy and fusion (ACDF). However, PEEK shows an inferior biological behavior regarding osseointegration and bioactivity. Therefore, the aim of the study was to create a bioactive surface coating on PEEK implants with a unique nanopore structure enabling the generation of a long-lasting interfacial composite layer between coating material and implant. Seventy-two PEEK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“… 32 Frankenberger et al . 33 found that the HA/SiO2‐based bioactive coating with interfacial composites on PEEK implants provided a lasting bone‐implant interface, and may be conducive to improving the property of bioinert surface of PEEK‐based implants. Addai et al .…”
Section: Bioactive Ceramicsmentioning
confidence: 96%
See 1 more Smart Citation
“… 32 Frankenberger et al . 33 found that the HA/SiO2‐based bioactive coating with interfacial composites on PEEK implants provided a lasting bone‐implant interface, and may be conducive to improving the property of bioinert surface of PEEK‐based implants. Addai et al .…”
Section: Bioactive Ceramicsmentioning
confidence: 96%
“…Therefore, these materials are usually used as surface coatings to improve the properties of PEEK, such as osseointegration and bioactivity. 32 Frankenberger et al 33 found that the HA/SiO2-based bioactive coating with interfacial composites on PEEK implants provided a lasting bone-implant interface, and may be conducive to improving the property of bioinert surface of PEEK-based implants. Addai et al 34 successfully prepared the reduced graphene oxide hydroxyapatite composite coating, significantly improving the hydrophilicity and bioactivity of PEEK.…”
Section: Bioactive Ceramicsmentioning
confidence: 99%
“…In recent years, PEEK implants have gone through three development phases: 1) mechanical property enhancement; 2) cytocompatibility and osteogenic ability enhancement; and 3) osseointegration and anti-inflammatory enhancement ( Gu et al, 2020 ). Improvement in PEEK properties is usually achieved through surface modification ( Frankenberger et al, 2021 ; Mehdizadeh Omrani et al, 2021 ; Jiang et al, 2022 ) and blending modification ( Ma et al, 2020 ; Ren et al, 2020 ; Hu et al, 2022 ). Waser-Althaus et al used oxygen and ammonia plasma to modify PEEK surfaces and enhance their hydrophilicity and protein adsorption capacity.…”
Section: Current Progress and Future Directionsmentioning
confidence: 99%
“…The repair of bone defects caused by trauma, tumors, and osteoarthritis was a prevalent conundrum in the medical field. , According to the investigation, surpass 2.2 million bone transplanted surgeries were performed annually worldwide to repair bone defects . Bone defects could trigger grievous hazards to patients, such as bone nonconnection, delayed healing, and functional disorders. Electrical stimulation was widely believed to be beneficial to promote bone repair since it could stimulate the release of growth factors, boost cell proliferation, and fortify extracellular matrix production to enhance osteoblast activity. , Currently, although electrical stimulation is frequently achieved through implanted electrodes, it usually requires complex external wiring and onerous power supply, which will undoubtedly cause discomfort and even secondary damage to patients. , Accordingly, it is urgent to construct a safe and efficient self-powered electrical stimulation strategy for promoting bone regeneration.…”
Section: Introductionmentioning
confidence: 99%